Screening of Cryoprotectants of Bacillus coagulans BC30 and Their Effect on the Digestive Tolerance of Bacteria Powder - Junjie LIU; Ningning CHEN; Yujuan XU; Jijun WU; Yuanshan YU; Jian PENG; Bo ZOU; Lu LI (Shipin gongye ke-ji)
In order to improve the viable bacterial count and digestion tolerance of Bacillus coagulans BC30 freeze-dried powder, the ratio of composite freeze-drying protective agent for B. coagulans BC30 was optimized by single factor experiment and response surface test. The protective effect of the optimal composite freeze-drying protective agent on B. coagulans BC30 was investigated, and the influence of the optimal composite lyoprotectant on the digestion tolerance of bacterial powder was revealed through simulated in vitro digestion. The results showed that the highest survival rate (91.43%) and viable count (1.60×1011 CFU/g) of B. coagulans BC30 freeze-dried powder were obtained when the protectants were composed of 9.6% skim milk powder, 10.9% fructooligosaccharide and 5.1% sodium glutamate, which were 51.43% and 1.29 times higher than that of B. coagulans BC30 freeze-dried powder without protectant, respectively. Scanning electron microscopy results exhibited that the surface of B. coagulans BC30 powder added with the optimal composite freeze-dried protectant was smooth and completely covered by the protectant. Meanwhile, the lactate dehydrogenase (LDH), extracellular galactosidase (β-GAL) and Na+-K+-ATPase activities of B. coagulans BC30 powder added with the optimal composite freeze-dried protectant were difference from those of B. coagulans BC30 powder added with single freeze-dried protectant. However, the lactate dehydrogenase (LDH), extracellular galactosidase (β-GAL) and Na+-K+-ATPase activities of B. coagulans BC30 powder added with the optimal composite freeze-dried protectant were similar to those of B. coagulans BC30 without freeze-drying, indicating that the cell membrane structure and function of B. coagulans BC30 added with the optimal composite freeze-dried protectant were better maintained. This result was also confirmed by cell sensitivity test and cell membrane fluidity analysis. After simulated digestion in vitro, the survival rate of B. coagulans BC30 powder added with the optimal compound freeze-drying protectant was 95.41%, which was 1.34 times that of the group without protectant. Above results indicated that the optimal composite freeze-dried protectant could reduce the freeze-drying damage on some key enzymes of B. coagulans BC30 by protecting its cell membrane, thereby improving the freeze-drying survival rate and digestion tolerance of B. coagulans BC30. The finding of this study provided a theoretical basis for the preparation of highly active and tolerant B. coagulans BC30 powder.